2017
DOI: 10.3386/w23576
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for Replication in Economics

Abstract: and participants in the 2016 BITSS annual meeting. Ada Kwan and Alexandra Wall provided excellent research assistance. The authors have no material or financial interests in the results of the paper. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This might be because replication studies are often treated as insufficiently novel for publication. In a survey, Galiani et al (2017) found that out of the 204 editors and co-editors of 11 top journals in economics, only 29% would publish replication studies confirming existing results.…”
Section: Introducing the Replication Studies Sectionmentioning
confidence: 89%
See 1 more Smart Citation
“…This might be because replication studies are often treated as insufficiently novel for publication. In a survey, Galiani et al (2017) found that out of the 204 editors and co-editors of 11 top journals in economics, only 29% would publish replication studies confirming existing results.…”
Section: Introducing the Replication Studies Sectionmentioning
confidence: 89%
“…The literature suggests two reasons for the lack of replication studies (Dewald et al, 1986;Galiani et al, 2017;Vilhuber, 2020):…”
Section: Introducing the Replication Studies Sectionmentioning
confidence: 99%
“…It is also important to validate the findings and detect potential biases in the existing literature. However, these exercises are not exempt from threats in that the replication itself is subject to incentives that may lead to biases, such as the “overturn bias”, where authors report false positives or claim mistakes in the original analysis without solid justifications (Galiani, Gertler, & Romero, 2017).…”
Section: Final Remarksmentioning
confidence: 99%
“…No strong conclusions can be drawn regarding possible editorial bias, but we think it worth mentioning, in part because publication bias is widely assumed to contribute to the inflated effect sizes among original findings. Galiani et al (2017) surveyed journal editors in economics and found that they preferred to publish failed rather than successful replications. Such a preference would be understandable, insofar as journal editors seek to preserve their much-sought-after journal space for new information that advances the field.…”
Section: Explaining Failuresmentioning
confidence: 99%